Exome Sequencing Identifies Susceptibility Loci for Sarcoidosis Prognosis - Lahtela, Elisa; Kankainen, Matti; Sinisalo, Juha; Selroos, Olof; Lokki, Marja-Liisa (Frontiers in Immunology, 2019)
Many sarcoidosis-associating immunological genes have been shown to be shared between other immune-mediated diseases. In Finnish sarcoidosis patients, good prognosis subjects more commonly have HLA-DRB1*03:01 and/or HLA-DRB1*04:01-DPB1*04:01 haplotype, but no marker for persistent disease have been found. The objective was to further pinpoint genetic differences between prognosis subgroups in relation to the HLA markers. Whole-exome sequencing was conducted to 72 patients selected based on disease activity (resolved disease, n=36; persistent disease, n=36). Both groups were further divided by the HLA markers (one/both markers, n=18; neither of the markers, n=18). The Finnish exome data from the Genome Aggregation Database was used as a control population in the preliminary sample. Statistical analyses included single-variant analysis for common variants and gene level analysis for rare variants. We attempted to replicate associated variants in 181 Finnish sarcoidosis patients and 150 controls. An association was found in chromosome 1p36.21 (AADACL3 and C1orf158), which has recently been associated with sarcoidosis in another WES study. In our study, variations in these genes were associated with resolved disease (AADACL3, p= 0.0001 and p=0.0003; C1orf158, p= 7.03E-05). Another interesting chromosomal region also peaked, Leucocyte Receptor Complex in 19q13.42, but the association diminished in the replication sample. In conclusion, this WES study supports the previously found association in the region 1p36.21. Furthermore, a novel to sarcoidosis region was found, but additional studies are warranted to verify this association.